Numerical and Experimental Analysis of Yb:YAG Thin Disk Regenerative Amplifier - Di Sun; Jie Guo; Wei Wang; Xiao Du; Yongxi Gao; Zichen Gao; Yan Liang (IEEE Photonics Journal, 2021)
We present an numerical and experimental analysis of a Yb:YAG thin disk regenerative amplifier. Group velocity dispersion, third order dispersion, and self-phase modulation (SPM) effects are considered in the simulations of the amplification process. By virtue of the simulations, a compact femtosecond Yb:YAG thin-disk chirped-pulse regenerative amplifier delivering an average power of 50 W at a central wavelength of 1030 nm with a propagation factor of M2 < 1.4 at a repetition rate of 200 kHz and a pulse duration of 500 fs was constructed. Numerical simulation based on this Yb:YAG thin-disk was carried out to investigate the pulse parameters evolution in each round trip. The measured experimental results in pulse width, spectrum, and pulse energy together fitted quite well with the numerical simulation. This plays an important role in the design of high-peak-power regenerative amplifier and will facilitate further power scaling and suppression of gain narrowing of the whole system.